YO HO HO AND A BUCKET OF CASH THE NEED TO ENCHANCE REGIONAL EFFORT TO COMBAT PIRACY AND ARMED ROBBERY AGAINST SHIPS IN SOUTHEAST ASIA - Mulyono, Hersapta (Indonesian Journal of International Law, 2014)
The problem of piracy is that the world press nowadays often focuses on waters off the coast of Somalia and the Gulf of Aden. That is understandable given the recent phenomenal upsurge of piratical activities in that poverty stricken part of the world. Poverty, alongwith degradation of the rule of law, is often a catalyst for criminal acts, and if that situation occurred in maritime neighborhood, it usually takes form of piracy and armed robbery against ships. Southeast Asia is one of those places. The primary purpose of this essay is to examine the deficiencies of regional efforts to combat piracy and armed robbery against ships in Southeast Asia. To provide readers with an understanding of the legal difficulties involved with piracy and armed robbery in Southeast Asia